Intratumoral heterogeneity: Role of differentiation in a potentially lethal phenotype of testicular cancer. Issue 12 (28th March 2016) - Tu, Shi‐Ming; Bilen, Mehmet Asim; Hess, Kenneth R.; Broaddus, Russell R.; Kopetz, Scott; Wei, Chongjuan; Pagliaro, Lance C.; Karam, Jose A.; Ward, John F.; Wood, Christopher G.; Rao, Priya; Tu, Zachary H.; et al.
Abstract : BACKGROUND: Intratumoral heterogeneity presents a major obstacle to the widespread implementation of precision medicine. The authors assessed the origin of intratumoral heterogeneity in nonseminomatous germ cell tumor of the testis (NSGCT) and identified distinct tumor subtypes and a potentially lethal phenotype. METHODS: In this retrospective study, all consecutive patients who had been diagnosed with an NSGCT between January 2000 and December 2010 were evaluated. The histologic makeup of primary tumors and the clinical course of disease were determined for each patient. A Fine and Gray proportional hazards regression analysis was used to determine the prognostic risk factors, and the Gray test was used to detect differences in the cumulative incidence of cancer death. In a separate prospective study, next‐generation sequencing was performed on tumor samples from 9 patients to identify any actionable mutations. RESULTS: Six hundred fifteen patients were included in this study. Multivariate analysis revealed that the presence of yolk sac tumor in the primary tumor ( P = .0003) was associated with an unfavorable prognosis. NSGCT could be divided into 5 subgroups. Patients in the yolk sac‐seminoma subgroup had the poorest clinical outcome ( P = .0015). These tumors tended to undergo somatic transformation ( P < .0001). Among the 9 NSGCTs that had a yolk sac tumor phenotype, no consistent gene mutation was detected. CONCLUSIONS: The current data suggest that intratumoral heterogeneity is caused in part by differentiation of pluripotent progenitor cells. Integrated or multimodal therapy may be effective at addressing intratumoral heterogeneity and treating distinct subtypes as well as a potentially lethal phenotype of NSGCT. Cancer 2016;122:1836–43 . © 2016 The Authors. Cancer published by Wiley Periodicals, Inc. on behalf of American Cancer Society. This is an open access article under the terms of the Creative Commons Attribution‐NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes. Abstract : Whether intratumoral heterogeneity is derived from differentiation of aberrant progenitor cells or from mutation of driver genes is investigated in a relevant clinical model, and the results suggest that intratumoral heterogeneity is caused in part by differentiation of pluripotent progenitor cells. Integrated or multimodal therapy may be effective at addressing intratumoral heterogeneity and treating distinct tumor subtypes as well as potentially lethal tumor phenotypes; this finding has profound clinical implications regarding the origin of intratumoral heterogeneity and the implementation of precision medicine in testicular cancer and other solid tumors.